The Influence of Cross Equatorial Northerly Surge (CENS) and El Niño Southern Oscillation (ENSO) on Atmospheric Dynamics in Western Indonesia - Togatorop, Jhon Paul Estomihi; Amri, Sayful; Sopacua, Jerremy Mezac (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2025)
Indonesia is located between the Asian and Australian continents, making its weather and climate significantly influenced by the atmospheric conditions of both continents. Differences in solar radiation received by high-latitude regions and the equator lead to pressure differences, resulting in airflows from high-pressure areas to low-pressure areas. This study analyzes atmospheric dynamics parameters during the occurrence of Cross Equatorial Northerly Surge (CENS) and El Niño Southern Oscillation (ENSO) in Neutral, La Niña, and El Niño phases. The analysis compares atmospheric dynamics during CENS-ENSO Neutral, CENS-La Niña, and CENS-El Niño events. The focus is particularly on part of the CENS propagation area, including the southern South China Sea to the western Java Sea. The data used in this study include ERA-5 reanalysis pressure level data, ERA-5 reanalysis single-level data, and CMORPH High-Resolution Global data with a spatial resolution of 0.25° x 0.25° and hourly temporal resolution. The results indicate that CENS during ENSO affects sea surface temperature, outgoing longwave radiation (OLR), precipitation, moisture transport, and divergence over Western Indonesia, particularly in southern Sumatra, the Java Sea, the northern coast of Java, and the western to southern coasts of Kalimantan.